P. acnes-Driven Disease Pathology: Current Knowledge and Future Directions - Leheste, Joerg R.; Ruvolo, Kathryn E.; Chrostowski, Joanna E.; Rivera, Kristin; Husko, Christopher; Miceli, Alyssa; Selig, Martin K.; Brüggemann, Holger; Torres, German (Frontiers in Cellular and Infection Microbiology, 2017)
This review discusses the biology and behavior of Propionibacterium acnes (P. acnes), a dominant bacterium species of the skin biogeography thought to be associated with transmission, recurrence and severity of disease. More specifically, we discuss the ability of P. acnes to invade and persist in epithelial cells and circulating macrophages to subsequently induce bouts of sarcoidosis, low-grade inflammation and metastatic cell growth in the prostate gland. Finally, we discuss the possibility of P. acnes infiltrating the brain parenchyma to indirectly contribute to pathogenic processes in neurodegenerative disorders such as those observed in Parkinson's disease (PD).